Implementing Employer Branding Using Agile Methodology - Aghababaei Barzegar, Roza (Digital Repository of Theses, 2025)
In an era of rapid digital transformation and intense competition, organizations face increasing pressure not only to innovate products but also to attract and retain top talent. This research explores the integration of Agile methodologies into employer branding strategies within the kitchen appliance manufacturing industry in Iran. The study aims to investigate how Agile-driven approaches influence employee engagement, satisfaction, retention, and employer brand attractiveness. Using a mixed-methods design, the research combined quantitative data from 124 survey responses with qualitative insights from 10 semi-structured interviews with industry leaders. Additionally, a content analysis of secondary data, including case studies from global firms such as Samsung, Siemens, Haier, and Whirlpool, was conducted to enrich the comparative framework. Quantitative analysis revealed that Agile practices in human resources are significantly correlated with improved employee retention (r = 0.72), satisfaction, and brand attractiveness. Regression models demonstrated that HR-marketing collaboration and feedback loops are strong predictors of employer branding success, with R² values ranging from 59.1% to 68.3%. Qualitative findings reinforced these results, highlighting themes such as cross-functional collaboration, real-time feedback integration, and iterative branding strategies. Secondary data validated these insights, showing that Agile branding leads to faster decision-making and greater workforce alignment. The research concludes that Agile methodologies provide a dynamic and responsive framework for employer branding, promoting adaptability, employee involvement, and strategic alignment with organizational goals. Despite clear benefits, challenges such as budget constraints and resistance to change remain prevalent. This study offers practical implications for HR professionals and organizational leaders, emphasizing the importance of agile collaboration, continuous feedback, and leadership commitment in crafting effective employer branding strategies. By integrating Agile principles into employer branding, companies can create more resilient and attractive workplaces that foster long-term engagement and competitive advantage in the evolving global labor market. The future research directions are proposed to expand, refine, and contextualize the insights generated by this study, particularly to cross-industry comparative studies, longitudinal research designs, exploration of cultural dynamics, and development of standardized measurement models. Keywords: Agile Methodology, Employer Branding, Employee Retention, Human Resources Strategy, Kitchen Appliance Industry